After the Death of God - Caputo, John D. (Insurrections : critical studies in religion, politics and culture., 2009)
It has long been assumed that the more modern we become, the less religious we will be. Yet a recent resurrection in faith has challenged the certainty of this belief. In these original essays and interviews, leading hermeneutical philosophers and postmodern theorists John D. Caputo and Gianni Vattimo engage with each other's past and present work on the subject and reflect on our transition from secularism to postsecularism. As two of the figures who have contributed the most to the theoretical reflections on the contemporary philosophical turn to religion, Caputo and Vattimo explore the changes, distortions, and reforms that are a part of our postmodern faith and the forces shaping the religious imagination today. Incisively and imaginatively connecting their argument to issues ranging from terrorism to fanaticism and from politics to media and culture, these thinkers continue to reinvent the field of hermeneutic philosophy with wit, grace, and passion.